Semantic and Structural Characteristics of Impersonal Sentences with Introductory “it” - Hovhannisian, Anahit (Armenian Folia Anglistika, 2006)
The article aims to reveal the nature of sentences with introductory it where the predicative is expressed by an adjective (it is…). The introductory it is followed by a compound nominal predicate with a predicative expressed by an adjective while the conjunction that introduces an object clause. The semantic aspect of these constructions is of certain interest, but it is also important to see through what English patterns it is expressed. Unlike the sentence It is a house, where the grammatical subject it preserves its deictic meaning, the pronoun it in the abovementioned sentences is fully abstracted and specified by the object clause. The adjective following the construction it is… acts as an epithet which expresses the person’s opinion and evaluation of the given action and reality. The nature of the grammatical noun – logical noun and subject – predicate correlations is also specified.